SOCIALIZED ACCOUNTS. - Littleton, A. C. (The Accounting Review, 1933)
Abstract The article focuses on socialized accounts in the United States. The author says that the industrial evolution is important in the United States. The new era of the twenties was real as its ideal of full production and abundant living is not lost. The first phase of the evolution of accountancy was likewise the longest. It consisted of two distinct movements. The earliest was concerned with the formation of the accounting mechanism or methodology-bookkeeping; the later movement covered the expansion of double-entry methodology to suit subsequent conditions. An account for money as well as goods is not difficult to reconstruct. A consciousness of proprietorship is more fundamental to the expansion of account-keeping into double entry bookkeeping than bilateral accounts, subtraction by contraentry, equality of debit and credit, or any the other peculiarities of double entry. The second phase of accountancy is related to attempts to secure some measure of control over private affairs in the social interest. The approach was through enforcing a partial sharing of otherwise private business data, of instituting, as it were, semi-public accounts. The third phase will probably carry the socialization of accounts still further.